Boronic Acid‐Mediated Activity Control of Split 10–23 DNAzymes. Issue 3 (15th December 2020) - Debiais, Mégane; Lelievre, Amandine; Vasseur, Jean‐Jacques; Müller, Sabine; Smietana, Michael
Abstract: The 10–23 DNAzyme is an artificially developed Mg 2+ ‐dependent catalytic oligonucleotide that can cleave an RNA substrate in a sequence‐specific fashion. In this study, new split 10–23 DNAzymes made of two nonfunctional fragments, one of which carries a boronic acid group at its 5′ end, while the other has a ribonucleotide at its 3′ end, were designed. Herein it is demonstrated that the addition of Mg 2+ ions leads to assembly of the fragments, which in turn induces the formation of a new boronate internucleoside linkage that restores the DNAzyme activity. A systematic evaluation identified the best‐performing system. The results highlight key features for efficient control of DNAzyme activity through the formation of boronate linkages. Abstract : Split, join, activate : Split DNAzymes made of two or more short nucleic acid strands are emerging as novel tools for biosensing applications. Herein, it is reported that the activity of 10–23 DNAzyme that was split into two nonfunctional fragments can be restored by formation of a boronate internucleoside linkage.